2017
DOI: 10.1016/j.msksp.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of static stretching on the shear elastic moduli of the medial and lateral gastrocnemius muscles in young and elderly women

Abstract: These results suggested that 5 min of SS might be effective for decreasing shear elastic modulus in both young and elderly women and that the effects on shear elastic modulus are similar between young and elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…In the present study, there was a significant decrease in RF stiffness after 5 min SS in adolescents. Similarly, Nakamura et al [19] and Taniguchi et al [20] and found a decrease in the stiffness of GM and gastrocnemius lateralis (GL) muscles after 5 min SS in adults using SWE. Akagi et al [16] found a significant decrease in GM muscle stiffness after 6 min of SS.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In the present study, there was a significant decrease in RF stiffness after 5 min SS in adolescents. Similarly, Nakamura et al [19] and Taniguchi et al [20] and found a decrease in the stiffness of GM and gastrocnemius lateralis (GL) muscles after 5 min SS in adults using SWE. Akagi et al [16] found a significant decrease in GM muscle stiffness after 6 min of SS.…”
Section: Discussionmentioning
confidence: 78%
“…Tissue stiffness measurements may be beneficial for the identification of muscles as well as a variety of organ disorders [13][14][15]. Elastography studies investigating the acute effects of stretching (ranging from 2-10 min duration) on the adult's triceps surae, hamstring and shoulder muscles have previously been performed [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, no study has investigated the acute effects of DS on SWS in elderly people and between genders. However, recent studies [ 100 ] have found no significant difference in MGM elasticity between men and women and between young and elderly women [ 101 ]. Recently Nakamura et al [ 101 ] suggested that the effect of 5 min of SS on decreasing shear elastic modulus is similar between young and elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching is a frequently used treatment to increase the range of motion of the ankle joints, and several studies have proved its effectiveness 1 , 2 , 3 , 4 ) . Various studies have focused their investigations on the biomechanical changes in muscles and tendons due to stretching, using ultrasonography imaging devices, and have shown that muscle stiffness is decreased with stretching 5 , 6 , 7 , 8 ) . In clinical practice, the therapist occasionally stretches the foot of the patient manually.…”
Section: Introductionmentioning
confidence: 99%